Down-regulation of ABCC11 protein (MRP8) in human breast cancer - Sosonkina, N.; Nakashima, M.; Ohta, T.; Niikawa, N.; Starenki, D. (Experimental Oncology, 2011)
Aim of this article is to investigate the expression of ABCC11 (MRP8) protein in normal breast tissue, and examine the difference in ABCC11 mRNA and protein expression between normal breast and breast cancer tissues taking into account ABCC11 genotype (a functional SNP, rs17822931) and estrogen receptor (ER) status.